Nekatera nova spoznanja o razvoju otroka - Toličič, Ivan (Obzornik zdravstvene nege, 1978)
The child’s mental development is inffuenced by numerous environmental factors involved in a dynamic interaction. Some studies of the effects of the changing environmental conditions, especially socio-economical family status entailed on the intellectual capacities, school success and certain leatures of the personality of the child are presented. The environment influences the child’s cognitive development too. These findings are ol great importance for the practical work, especially a systematic preschool education.